Effect of exercise interventions on perceived fatigue in people with multiple sclerosis: synthesis of meta-analytic reviews. (June 2017) - Safari, Reza; Van der Linden, Marietta L; Mercer, Tom H
Although exercise training has been advocated as a nonpharmacological treatment for multiple sclerosis (MS) related fatigue, no consensus exists regarding its effectiveness. To address this, we collated meta-analytic reviews that explored the effectiveness of exercise training for the treatment of MS-related fatigue. We searched five online databases for relevant reviews, published since 2005, and identified 172 records. Five reviews were retained for systematic extraction of information and evidence quality analysis. Although our review synthesis indicated that exercise training interventions have a moderate effect on fatigue reduction in people with MS, no clear insight was obtained regarding the relative effectiveness of specific types or modes of exercise intervention. Moreover, Grading of Recommendation Assessment, Development and Evaluation revealed that the overall quality of evidence emanating from these five reviews was 'very low'.